Developing Trilingual Supplementary Learning Materials to Enhance First-Grade Elementary Students’ Receptive and Productive English Language Skills - Dewantara, Kadek Andre Karisma (International Journal of Language and Literature, 2024)
One of the key factors contributing to the ineffectiveness of language learning in schools is the limited availability of resources, including textbooks, teaching materials, and other essential tools required for effective English language instruction. Therefore, additional learning materials are needed to supplement the deficiencies of classroom teaching resources in English language learning. This study aims to develop supplementary trilingual learning materials to facilitate students' receptive and productive English language skills in first-grade elementary school. This research follows a development approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data were collected using a Likert scale questionnaire involving two experts. The research employed a quantitative descriptive analysis method. The developed prototype of the supplementary learning materials consists of six chapters with a total of 75 pages. The materials are designed to be engaging, featuring illustrations, audio for listening skills, games, and vocabulary tables in each chapter. The use of specially designed supplementary materials to enhance receptive skills (listening and reading) and productive skills (speaking and writing) in English is expected to make a significant contribution to improving students' English proficiency.